GAME EDUKASI METAMORFOSIS HEWAN BERBASIS ANDROID SEBAGAI MEDIA PEMBELAJARAN DI SDN 41 PALEMBANG - Meliza; Saputra, Herlambang; Prambayun, Arif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Animal metamorphosis requires clear visualization because it involves gradual changes in an animal’s body form. The use of technology through educational games can serve as an alternative learning medium that presents learning materials in an interactive and engaging manner. This study aimed to develop an Android-based educational game on animal metamorphosis as a learning medium for third-grade students at SD Negeri 41 Palembang. The game was developed using the Game Development Life Cycle (GDLC) method, which consists of the initiation, pre-production, production, internal testing, and release stages. In addition, the Finite State Machine (FSM) algorithm was implemented to control the behavior of enemy NPCs through the Patrol, Chase, Attack, and Recall states. The results of functional testing, player control testing, and gameplay testing showed that all game features operated according to the design specifications. FSM testing achieved a success rate of 100%, which was categorized as very good. System performance testing using Unity Profiler showed an average frame rate of 115.26 FPS, CPU usage of 9.04 ms, and memory (RAM) usage of 1.18 GB, with no lag or freezing observed during testing. The learning evaluation results showed an increase in the students’ average score from 50.77 in the pre-test to 89.85 in the post-test. The average N-Gain score was 0.85 or 85%, which was categorized as high. Based on these results, the developed Android-based educational game on animal metamorphosis was considered effective and feasible for use as a learning medium to help improve third-grade students’ understanding of animal metamorphosis at SD Negeri 41 Palembang.